The effects of rivaroxaban, an oral anticoagulant, on human IVD primary cultures - Tezcan Caliskan; Hande Akalan; Ibrahim Yilmaz; Numan Karaarslan; Duygu Yasar Sirin; Hanefi Ozbek (Archives of Medical Science, 2021)
Introduction The present study aimed to investigate the potential effects of rivaroxaban, an oral anticoagulant that inhibits the effects of factor Xa, on intact intervertebral disc tissue cells and the extracellular matrix (ECM).